Pathways to Get Help: Help-Seeking on College Students with Non-Suicidal Self-Injury - Zahrah Humaidah Emqi; Nurul Hartini (Universitas Muhammadiyah Enrekang, 2022)
This study aimed to identify and explore the aspects that encourage and inhibit students who do non-suicidal self-injury (NSSI) in seeking help. The research method used is qualitative research with a phenomenological approach to determine participants' subjective experiences. Researchers conducted in-depth interviews with students aged 20-21 who had done NSSI. The participant-checking technique carries out the method of strengthening the credibility of the data. The results of the interpretive phenomenological analysis identified five themes in the participants' experiences, including self-awareness, self-disclosure, mental health literacy, stigma, and social influence. Awareness of the problem, positive expectations of self-disclosure, and knowledge and belief in the availability of help can be the impetus for seeking help. These aspects interact with stigma and social influence, so the decision to seek help becomes complex. This study provides information about the importance of mental health literacy and strengthening in dealing with negative stigma about people with mental health problems.